Seashore Explore nature with fun facts and activities - Burnie, David; consultant: John wood ward (London D.K. Publishing, 2017)
A fantastic first book on the coast, this book is the perfect companion for children eager to understand the world of the shoreline. Explore the beach and find out about shell shapes, what lives in rockpools, and find out the answer to questions such as ""What causes tides?"" With exciting activities, like making a paper boat, and plenty of fun facts, Nature Explorers: Seashore is a must-have for children curious about the seashore and keen to explore the world. About the series: The Nature Explorers series is a fantastic first set of books on the great outdoors for children aged 6 to 8. From birds, to weather, to the seashore, and more, the key topics of each subject are explained with plenty of fun activities to do along the way, encouraging kids to investigate and record everything they see.
Keywords: Science informative book